The development of interactive systems: bridging the gaps between developers and users - Grudin, Jonathan (DAIMI Report Series, 1990)
A framework for interactive systems development projects is outlined. Three development paradigms are contrasted: competitively bid contract development, product development, and in-house or custom development. They vary as to when in a project the users and the developers can be identified – a distinction that is particularly significant for systems with a human-computer interface component. The historical influence of each of these paradigms on interactive systems development is reviewed. Other factors affecting the flow of information between users and developers are outlined. For each development paradigm, I identify the opportunities for adopting an effective ’’user focus,’’ the obstacles, and the mediators who contribute to bridging the gaps between developers and users.